Development of a prognostic model for children with neuroblastoma based on necroptosis-related genes - Jing Chu, (Frontiers in Genetics, 2022)
Background: Neuroblastoma (NBL) is a rare malignant tumor of the peripheral sympathetic nervous system in children with a low overall survival rate. Recent studies have revealed the important role of necroptosis in the occurrence and development of many kinds of tumors. In this study, a prognostic model based on necroptosis-related genes was constructed for NBL. Methods: Expression profiles and clinical information for patients with NBL were downloaded from TARGET. Data for necroptosis-related genes were extracted for Cox regression and lasso regression analyses to evaluate factors associated with prognosis and to construct a prognostic model. Data from the GEO datasets GSE62564 and GSE85047 were used for external verification. Associations between risk scores were calculated, and immune infiltration, drug sensitivity, and mutation analyses were conducted. Functional enrichment analyses of genes in the prognostic model were performed. Results: Six necroptosis-related genes (i.e., CYLD, JAK1, APC, ERH, CNBP, and BAX) were selected to construct a prognostic risk model. The risk score was highly correlated with levels of infiltration of multiple immune cells and sensitivity to common antineoplastic drugs. In addition, the risk score was identified as an independent prognostic factor for patients with NBL. Conclusion: We constructed and validated a prognostic model based on necroptosis-related genes, providing insights into the development and progression of NBL and a basis for improved management. In addition to providing a tool for clinical decision-making, these findings support the importance of necroptosis in NBL and may guide the development of therapeutic strategies targeting this process.